2009
DOI: 10.1002/ls.102
|View full text |Cite
|
Sign up to set email alerts
|

Friction evaluation of elastomers in lubricated contact

Abstract: Friction testing of elastomers in lubricated contact is discussed with a focus on developing experimental arrangements that can produce worthwhile results. Practical issues unique to elastomers are covered as well as their solutions, including contact mechanics, material response to loading, contact edges, oil absorption, cleaning and specimen geometry. A critique of reciprocating laboratory testing machines, including high-frequency short stroke and low-frequency long stroke friction and wear machines, is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…15 Very low normal load can induce deformation of the elastomer, which indicates that their friction is related to the internal friction of the elastomer. 12 Consequently, the friction force exerted by an elastomer is mainly related to its bulk properties. 15 The friction force between the elastomer and hard counterface materials are commonly described as being comprised of a hysteresis and an adhesion component.…”
Section: Tribology Of Elastomersmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Very low normal load can induce deformation of the elastomer, which indicates that their friction is related to the internal friction of the elastomer. 12 Consequently, the friction force exerted by an elastomer is mainly related to its bulk properties. 15 The friction force between the elastomer and hard counterface materials are commonly described as being comprised of a hysteresis and an adhesion component.…”
Section: Tribology Of Elastomersmentioning
confidence: 99%
“…19 Previous tribological studies of NBR have been mostly focused on tests under dry friction conditions [20][21][22] and only a few investigations have been conducted on their frictional behaviors after ageing in lubricants. 12,13 Recently, Myant et al 23 reported how applied load and elastic properties of elastomers will influence the rolling and sliding friction of lubricated compliant contacts using a mini traction machine. However, most of the applications for nitrile rubbers are in those where the elastomer is exposed to different lubricating oils.…”
Section: Tribology Of Elastomersmentioning
confidence: 99%
See 1 more Smart Citation